Real-time Implementation of Space Vector Modulation using Arduino as a Low-cost Microcontroller for Three-phase Grid-connected Inverter - Amal Satif; Laamari Hlou; Abdelkarim Zemmouri; Hamad Dahou; Rachid Elgouri (IAES Indonesian Section, 2020)
This work aims to facilitate the approach of a promising and fascinating technology, which is the photovoltaic (PV) energy, concerning the integration of PV systems to the utility grid from the control/synchronization point of view. Within this context, this paper gives a performance analysis of modeling and driving a two-level three-phase grid-connected PV system, in order to reduce the variations in frequency and phase, as a result, the synchronization between the inverter and the utility grid is accomplished and the correct function of the inverter is performed. MATLAB/Simulink software was utilized to develop the model of the suggested control algorithms. Then, as an interfacing device between the software and the inverter, the Arduino UNO microcontroller is proposed as a low-cost and simplified method to control the three-phase grid-connected inverter